A statistical quality control study on Star Paper Corporation - Endaya, Victor Carlo (College of Engineering, 1999)
This study focuses on the quality system of the factory of Star Paper Corp. in 46 Joy St., Grace Village, Quezon City. This study was conducted during June to October 1998. The existing quality system of the factory was documented and evaluated. Observations were made by the Industrial Engineering students with the aid of the production supervisor of Star Paper Corp. The study is limited to the sheeting process of Star Paper's operations. This was advised by the production supervisor, since this is the process which generate the most defects of Star Paper. Analysis of the sheeting process showed that the variation in the output of the sheeting process, is caused by the sheeting machine themselves. Wiuth the use of DMRT, it was recognized that the machines 1 and 2 caused the vriation in the process, hence, causing the majority of defects. The magnitude of the variation of the sheeting process was then represented by using control charts that showed the percent defects per day of Star Paper's sheeting machines. IT was observed that machine 2 had a high mean defect rate. The main reason for this is that the machine is old and had inherent machine defects which could not be isolated. Recommendations were generated with the aim of determining the maximum amount to be spent to justify the replacement of a defective sheeting machine. Further recommendations were formulated with the aim of improving the quality control in the sheeting process.